ELASTISITAS KESEMPATAN KERJA PADA SEKTOR PERDAGANGAN, HOTEL DAN RESTORAN DI KABUPATEN LANDAK - B01108037, HENDRI (Jurnal Pembangunan dan Pemerataan, 2015)
AbstractThis. Research quiet elasticity of employment in trade, hotels and restaurants in the District Landak.penelitian aims to determine To determine the elasticity of employment and employment in trade, hotels and restaurants in the district Landak 2008-2012.The method used in this research is descriptive method, the method used to solve problems based on an idea or study as well as facts and data are available. Quantitative methods are methods that look at the relationship between economic growth on employment, then using the model of employment elasticity between the growth of employment opportunities with the growth of national income.Research trade, hotels and restaurants have the elasticity of employment (> 1), which amounted to 1,38 percent. Contributions given by sub-sector, trading at 21.53 percent. While the sub-sector that contributes the smallest trade sub-sector is the Hotel at 0.13 percent in 2012.Keyword: elasticity, employment, employment opportunities.